Neoplasia Trofoblastik Gestational Pasca-Mola pada Wanita Usia 25 Tahun - Satria Kusuma, Nur Huda; Wildan Aulia Firdaus (Fakultas Kedokteran Universitas Andalas, 2025)
Introduction: Hydatidiform mole is the most common gestational trophoblastic disease in regions such as Asia, Africa, and Latin America, with a lower incidence in European countries. In Indonesia, the incidence ranges from 1 in 100 to 141 pregnancies, particularly affecting women under 20 and over 45 years old, often in those with low socio-economic status and nutritional deficiencies (such as protein, folic acid, and carotene). Case Presentation: A 25-year-old female presented to Malang City General Hospital with complaints of recurring brownish-black foamy vaginal discharge, nausea-vomiting for two months. She had regular menstrual cycles and no contraception use. On examination, the uterine fundal height was one finger above the symphysis pubis with no fetal heart sounds or uterine contractions. Vaginal examination revealed a closed cervix and foamy black blood. Ultrasound showed a retroverted uterus, a 6.4 mm gestational sac without a fetal pole, 37.0×31.6mm residual tissue, a honeycomb pattern, and no myometrial invasion. Blunt curettage removed 30 grams of bubble-like tissue. Histopathology confirmed a complete hydatidiform mole. β-hCG levels and uterine size continued rising post-curettage. Discussion: A significant number of low-risk PGTN patients with a FIGO score of 0-6 show a complete response to first-line methotrexate/folinic acid therapy. However, those with a score of 6 or β-hCG levels >100,000 IU/l have a higher resistance rate. Despite this, the survival rate remains very high. Conclusion: PGTN is a malignant uterine tumor linked to molar pregnancies. Single-agent chemotherapy remains the standard treatment and has a generally favorable prognosis.